Technology Leadership in Native American Schools - Jayson W. Richardson; Scott McLeod (Journal of Research in Rural Education, 2011)
Principals of schools serving Native American students have a unique role as technology leaders. They must be cognizant of technological demands, government mandates, as well as unique societal and cultural needs. In this study, the researchers conducted interviews with nine principals in federally-funded, Bureau of Indian Education schools that serve Native American students to explore various topics related to technology leadership as described by the National Educational Technology Standards for Administrators (NETS-A). We find that these principals are meeting various components of the NETS-A in unique ways but are missing many components of the standards entirely. We find that a lack of professional development on technology training, a dearth of technology coordinators, poverty, and isolation were major challenges to their technology leadership. We conclude that the field of educational leadership must respond to the needs of the marginalized communities to meet their unique demands by focusing on relevant technology leadership training through preparatory and in-service training.